Influence of Work Discipline and Work Motivation on Employee Performance (Study on Universitas Brawijaya Malang Republic of Indonesia Employee Cooperative) - Ratna Nikin Hardati (Universitas Negeri Makassar, 2021)
The purpose of this study is to (1) examine and explain the influence of work motivation on employee performance, (2) examine and explain the influence of work discipline on employee performance, (3) examine and explain the influence of work motivation and work discipline on employee performance. This study was conducted at the Republic of Indonesia Employee Cooperative, Brawijaya University, Malang (KPRI UB Malang). The approach used is a quantitative approach with two independent variables, i.e., work motivation and work discipline, and one dependent variable, employee performance. This study uses a survey method by distributing questionnaires to members of the Republic of Indonesia Employee Cooperative, Universitas Brawijaya Malang. Data analysis was performed by Smart PLS software version 3.2.8 through evaluating the outer model and inner model. This study found that work motivation has no influence on employee performance, but on the contrary, work discipline has a positive influence on employee performance of KPRI UB Malang. In addition, work motivation and work discipline simultaneously influence employee performance.